Indigenous People and Contested Access to Land in the Philippines and Indonesia - Rutten, Rosanne (Kasarinlan: Philippine Journal of Third World Studies; Vol 30, No 2-Vol 31, No 1 (2015-2016): Indigenous People and Contested Access to Land, 2017)
To provide context to the articles and research notes in this issue, this introduction presents contrasting and converging trends in indigenous communities’ troubled access to land in the Philippines and Indonesia. Moreover, it highlights the main themes discussed in this issue, in particular: histories of dispossession; state recognition of indigenous people’s land rights (and its challenges); dilemmas of inclusion and exclusion; communal versus individual land ownership trends; and patterns of resistance, negotiation, and accommodation.